PERLINDUNGAN PENUMPANG KECELAKAAN KERETA API DI DAERAH OPERASI 4 SEMARANG - Adelia Dwi Agata (Jurnal Ilmiah Dinamika Hukum, 2020)
Accidents on the way, are something that is not expected, but if they happen, we cannot avoid them. Likewise with train accidents. Therefore it is necessary to research, in the event of a train accident, whether PT KAI Indonesia, in this case the Daop 4 Semarang area, has carried out its obligations. This study aims to discuss the issue of passenger protection related to Indonesian train accidents in the Operational Area 4 Semarang.The research method used is juridical normative, with descriptive research specifications. Obtaining data using secondary data through library research and interview techniques as a complement to secondary data which is then analyzed using descriptive qualitative methods.The results showed that PT. Indonesian Railways Operational Area 4 Semarang has carried out its responsibilities and obligations in accordance with Article 87, Article 157, Article 167 Law No. 23 of 2007 concerning Railways, namely carrying out evacuations as soon as possible, hiring to the nearest hospital, providing compensation with varying amounts between IDR 500 thousand to IDR 50 million. For passengers, they can also take legal remedies, namely by way of deliberation, conciliation, mediation and arbitration, even though in reality what is being done is filing a class action lawsuit. PT. Kereta Api Indonesia, Operation Area 4 Semarang, is that there are still many passengers who do not understand how to claim Jasa Raharja compensation for accident victims. Another obstacle is the incomplete requirements for PT. Raharja services submitted by passengers. Keywords: PT Kereta Api Indonesia, Accident, Responsibility